The impact of teaching games for understanding and direct instruction models on volleyball passing skills based on arm strength - Ciptadi, Zaniar Dwi Prihatin; Nugroho, Sigit; Adriani, Desi; Singh, Laishram Thambal (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. The Teaching Games for Understanding (TGFU) model emphasizes tactical understanding of the game, while Direct Instruction is more oriented towards explicit instruction and repetitive practice. Therefore, this study aims to analyze the effect of TGFU and Direct Instruction learning models on volleyball lower passing skills based on students' arm strength.Material and Methods. This study used an experimental design with a 2x2 factorial design, involving two independent variables, namely the learning model (TGFU and Direct Instruction) and arm strength (high and low). The sampling technique used was random sampling based on the results of the initial test or pretest and obtained 36 as a sample. Statistical tests used include the Shapiro-Wilk normality test, Levene's homogeneity test, and hypothesis testing using the Paired t-test, Wilcoxon, Independent Samples Test, and ANOVA with the help of SPSS 26.Results. The results of the analysis showed that both learning models (Teaching Games for Understanding and Direct Instruction) had a significant effect on volleyball lower passing skills (p<0.05). However, there is no significant difference between the two learning models (p>0.05), so both have the same effectiveness in improving passing skills. Meanwhile, arm strength showed a significant difference on volleyball passing skills (p=0.000), confirming that this physical factor plays a role in learning outcomes.Conclusions. The results of this study can be used as a reference for educators and coaches in designing learning methods that are more effective and in accordance with the physical characteristics of students. By understanding the interaction between learning models and arm strength, it is hoped that the volleyball learning process can be optimized, so that students can achieve better performance in lower passing skills.